If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -2) = 60 Reorder the terms: 6(-2 + x) = 60 (-2 * 6 + x * 6) = 60 (-12 + 6x) = 60 Solving -12 + 6x = 60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 6x = 60 + 12 Combine like terms: -12 + 12 = 0 0 + 6x = 60 + 12 6x = 60 + 12 Combine like terms: 60 + 12 = 72 6x = 72 Divide each side by '6'. x = 12 Simplifying x = 12
| (5,-4)6-2=5 | | p^2-5p+6=0 | | 5b+6b+2=19 | | 7j-8j=1 | | 9+3b=50 | | (2)x+6+x+5+x=91 | | 8m^2+12mn=0 | | X-32=73 | | x^2+15x-46=0 | | 3x+4(3+2x)=11x-12 | | -6n+21=6n-3 | | 3(m-2)=.25(12m+24) | | N*7-1=4 | | 4x-23=8x-7 | | 105x^6+55x^5-10x^4=0 | | 4x+9=x-3 | | 3x^2-3=8x | | 45x^2-56x-45=0 | | 8x+5-x=-1 | | 1.5z=85 | | 3x^2-3=8u | | 4n+5-6n=7 | | 48+(-5x)=-7 | | -x^2-13x-2=0 | | y=2x^4-3x^3-17x^2-27x-81 | | X^2+30x+15=-75 | | 42=18-4c | | -t^2+8t-16=0 | | 2x-10=12x-45 | | 15=7-y | | (2x-250)+x=890 | | (2x-250)+x= |